OVERVIEW MASLAHAH ON APPLICATION ISLAMIC SHARIA IN INDONESIA ACCORDING TO INDONESIAN HIZBUT TAHRIR - Khasanah, Uswatul; Rosyid Ridho, Muhammad; Eri Sofiana, Neng (Jurnal Ad Dustur, 2024)
Hizbut Tahrir Indonesia is a community organization that has existed in Indonesia which is unique in its desire to apply sharia principles in every regulation in Indonesia. According to them, in order for these ideals to be realized, there must be a supporting institution whose function is to control it, namely al-khilafah al-Islamiyah. The concept of al-khilafah al-Islamiyah must of course be based on the concept of the benefit of the ummah. Based on this, the researcher will outline HTI's views regarding the implementation of Islamic law in Indonesia from a maslahah perspective. This research is qualitative using library methods. Researchers obtained data from various library sources such as books, journals and other media related to the application of Islamic law in Indonesia and analyzed deductively. Based on this research, it can be seen that HTI is the only institution capable of exercising power that implements the Islamic sharia system in a pure and comprehensive manner, only with the al-khilafah. Second, according to maslahah theory, the idea of ​​HTI is considered to be contrary to the objectives of Islamic law, namely hifdz an-din or hifdz al-huriyyah al-I'tiqad. Third, in the Indonesian context, the application of sharia will be beneficial if it is applied in the form of civil society. The application of sharia in the Indonesian context places greater emphasis on maqosid al-tasyri' and hikmah al-tasyri'.